Local and Social Dynamics in Innovation Ecosystems: The Case of the Video Game Industry in Montreal - Rampa, Romain; Simon, Laurent; Manent, Margaux (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This paper aims at a better understanding of the dynamics behind the concept of innovation ecosystems. We argue that interactions and interdependencies between the various actors of an ecosystem cannot be thought of as solely resulting from a complex arrangement of formal linkages. These dynamics cannot be disconnected from the local environment in which they are embedded, as this environment will be expected to provide a variety of resources that cannot be formally controlled by the actors of the system, and yet are key in driving the regeneration and attraction capacities of innovation ecosystems. Our results show that informal local platforms of interactions and various communities play a major role in this interplay.